Application Of a Combination of AHP and TOPSIS Methods in Shipyard Selection - Iman Taufiq Daulay; A.A.B. Dinariyana (International Journal of Marine Engineering Innovation and Research, 2023)
Choosing a shipyard that does not meet the requirements can affect ship building process. Incompatibility of construction process can cause delays in completion time or delivery of ship to shipowner. The resulting delays can affect reputation of shipowner because they cannot fulfill their cargo delivery services, where cargo contract is generally carried out before ship is handed over from shipyard to shipowner. Delays will also affect insurance providers, both ship and cargo insurance. A stricter evaluation from insurance company could result in an increase in premiums charged due to risks that will be faced in the future. The aim is to determine priority of shipyards that will be appointed for ship construction in Batam area. Because shipyard selection does not only involve quantitative but also qualitative variables, Multi-Criteria Decision Making (MCDM) method was used in this research. Method used in selection is a combination of Analytical Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS). AHP is used to determine weight of the criteria and sub-criteria used in selection, while TOPSIS is used to determine shipyard selection priorities based on weight of criteria and sub-criteria that have been generated from AHP process. Respondents in this study were representatives of three ship owners, consisting of two technical managers and one deputy general manager. Based on the results of the analysis of six shipyards in Batam area, a priority order of shipyards recommended for ship construction by company was obtained. Sensitivity analysis also shows that the results produced in shipyard selection are quite robust.